IMPROVING STUDENTS ABILITY IN SPEAKING DESCRIPTIVE TEXTBY USING MIND MAPPING - Fitra Murni AR (English Language Teaching and Research, 2017)
This classroom action research was conducted to see the improvement of students’ ability in speaking descriptive text by using mind mapping. The research was done at the first year 7 (X7) SMAN 3 Padang Panjang in the 2015/2016 academic year in two cycles. There were twenty nine students in this class. The data were collected through pre-test, formative test and observation. The students were led to speak descriptive text by using mind mapping and guided to speak it well. Through observation and formative test, it seemed that the students liked and enjoyed speaking descriptive text. It could be seen from their achievement improved from cycle to cycle and their test results. The improvement got was 61 % in the first cycle and 78 % in the second cycle. In conclusion, the students’ speaking ability can be improved if they know and understand what and how to speak and the use of the appropriate teaching aids is very important. One of the teaching aids that can be used to improve students’ ability in speaking descriptive text is mind mapping. It is suggested to English teachers to use mind mapping in teaching speaking descriptive text. Keywords: speaking, descriptive text, mind mapping